The The utilization of social media in students’ writing skill - Azziza, Melenia Nisa'ul (Indonesian Journal of Multidisciplinary Educational Research, 2025)
This study explores the role of social media in students' writing development, focusing on the platforms they use and their perceptions of its effectiveness. Using a descriptive qualitative approach, data were gathered from thirty eighth-grade students at SMP Islam Srengat through questionnaires and interviews. The findings show that TikTok is the most widely used platform for learning, with 36.7% of students using it, followed by Instagram (30.0%), YouTube (23.3%), Facebook (6.7%), and Twitter (3.3%). While 43.3% of students find social media beneficial for improving their writing skills, 33.3% consider it quite useful, and 20% rate it as very helpful. However, some students remain neutral or disagree, often due to parental restrictions. The study highlights social media's potential as a valuable educational tool, while acknowledging that its impact on writing development varies depending on individual factors, such as student motivation, access to digital tools, and parental control.